Decision-making dilemmas of paediatricians: a qualitative study in Japan. Issue 8 (19th August 2019) - Sasazuki, Momoko; Sakai, Yasunari; Kira, Ryutaro; Toda, Naoko; Ichimiya, Yuko; Akamine, Satoshi; Torio, Michiko; Ishizaki, Yoshito; Sanefuji, Masafumi; Narama, Miho; Itai, Koichiro; Hara, Toshiro; et al.
Abstract : Objective: To delineate the critical decision-making processes that paediatricians apply when treating children with life-threatening conditions and the psychosocial experience of paediatricians involved in such care. Design: We conducted semistructured, individual face-to-face interviews for each participant from 2014 to 2015. The content of each interview was subjected to a comprehensive qualitative analysis. The categories of dilemma were extracted from a second-round content analysis. Participants: Participants were board-certified paediatricians with sufficient experience in making decisions in relation to children with severe illnesses or disabilities. We repeated purposive sampling and analyses until we reached saturation of the category data. Results: We performed interviews with 15 paediatricians. They each reported both unique and overlapping categories of dilemmas that they encountered when making critical decisions. The dilemmas included five types of causal elements: (1) paediatricians' convictions; (2) the quest for the best interests of patients; (3) the quest for medically appropriate plans; (4) confronting parents and families and (5) socioenvironmental issues. Dilemmas occurred and developed as conflicting interactions among these five elements. We further categorised these five elements into three principal domains: the decision-maker (decider); consensus making among families, colleagues and society (process) and the consequential output of the decision (consequence). Conclusions: This is the first qualitative study to demonstrate the framework of paediatricians' decision-making processes and the complex structures of dilemmas they face. Our data indicate the necessity of establishing and implementing an effective support system for paediatricians, such as structured professional education and arguments for creating social consensus that assist them to reach the best plan for the management of severely ill children.